2010
DOI: 10.1002/cne.22261
|View full text |Cite
|
Sign up to set email alerts
|

Effects of incisor extraction on jaw and tongue motor representations within face sensorimotor cortex of adult rats

Abstract: Loss of teeth is associated with changes in somatosensory inputs and altered patterns of mastication, but it is unclear whether tooth loss is associated with changes in motor representations within face sensorimotor cortex of rats. We used intracortical microstimulation (ICMS) and recordings of cortically evoked muscle electromyographic (EMG) activities to test whether changes occur in the ICMS-defined motor representations of the left and right jaw muscles [masseter, anterior digastric (LAD, RAD)] and tongue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
50
1
3

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 76 publications
9
50
1
3
Order By: Relevance
“…Analysis using positron emission tomography and magnetic resonance imaging has shown that chewing increases neuronal activity in various regions of the cerebral cortex. 6 It has reported that dental extraction may be associated with significant neuroplastic changes within the rat's face primary motor cortex and adjacent face primary somatosensory cortex that may be related to the animal's ability to adapt to the altered oral state 7 and the maturation of network function in the oral somatosensory cortex is impaired by tooth loss during the developmental period. 8 Epidemiological studies have revealed that tooth loss is a risk factor for senile dementia.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis using positron emission tomography and magnetic resonance imaging has shown that chewing increases neuronal activity in various regions of the cerebral cortex. 6 It has reported that dental extraction may be associated with significant neuroplastic changes within the rat's face primary motor cortex and adjacent face primary somatosensory cortex that may be related to the animal's ability to adapt to the altered oral state 7 and the maturation of network function in the oral somatosensory cortex is impaired by tooth loss during the developmental period. 8 Epidemiological studies have revealed that tooth loss is a risk factor for senile dementia.…”
Section: Introductionmentioning
confidence: 99%
“…Unilateral transection of the lingual nerve supplying sensory innervation to the rat's tongue results in significant time-dependent changes of the anterior digastric and genioglossus representations within face MI, 1-4 weeks later [103]. In addition, extraction of a mandibular incisor in rats is associated 1 week later with significant neuroplastic changes within the contralateral face MI that are manifested as a significant expansion of the ICMS-defined anterior digastric motor representation (Table 1) [8,31]. Trimming both rat mandibular incisors also induces face MI neuroplastic changes but this is reflected as a significant reduction in the anterior digastric representation in face MI that can be restored if the incisors are allowed to erupt back into occlusion [8].…”
Section: Face MImentioning
confidence: 96%
“…1). Short-train ICMS can also evoke jaw and tongue movements when applied to the face SI or face MI in subprimates [26][27][28][29][30][31]. On the other hand, longtrain ICMS can evoke semiautomatic movements such as mastication, swallowing and facial whisking from the face MI and face SI of monkeys and subprimates [19][20][21][22][32][33][34].…”
Section: Overview Of Orofacial Sensorimotor Circuits and Role Of Facementioning
confidence: 96%
See 2 more Smart Citations